Tumor necrosis factor mRNA localized to Paneth cells of normal murine intestinal epithelium by in situ hybridization. - Keshav, S; Lawson, L; Chung, L; Stein, M; Perry, V; Gordon, S (1990)
Paneth cells in normal murine small intestine contain TNF mRNA that is readily detectable by in situ hybridization, unlike resident macrophages in lamina propria, which are negative. Northern blot analysis of whole tissue shows the presence of mRNA that has the same electrophoretic mobility as TNF mRNA from activated macrophages. A low level of TNF bioactivity, but no immunoreactivity, was detected in normal small intestine, and TNF production in resting Paneth cells appears to be post-transcriptionally controlled. Typical leukocyte surface membrane markers were not found on Paneth cells, but were expressed by the surrounding lamina propria macrophages. Paneth cells are thus epithelial cells with leukocyte-like secretory potential that may be important in intestinal physiology and pathology.